الدعم الكويتي للثورة الجزائرية 1954 م - 1962 م - فايد، بشير رابح Fayed, Bashir Rabah (جامعة الأمير عبد القادر للعلوم الإسلامية, 2017)
تستهدف هذه الورقة، تسليط الضوء على مختلف أشكال الدعم السياسي والمالي والثقافي والإعلامي والإنساني، التي قدمتها الكويت الشقيقة رسميا وشعبيا للثورة التحريرية الجزائرية 1954م – 1962م، لاعتبارات دينية وقومية وعاطفية وإنسانية، ومن دون شرط أو مقابل كما فعل البعض، نصرة للشعب الجزائري المضطهد والمقهور، في كفاحه من أجل افتكاك حريته وتحقيق سيادته على أرضه، وبناء دولته الوطنية التي حلمت ما أجيال من المقاومين والمناضلين والجاهدين وقوافل من الشهداء، غير آبهة بالضغوط والتهديدات المختلفة، التي كانت تمارسها وتطلقها السلطات العليا الفرنسية، ضد كل من يجرأ من الدول أو الحكومات أو الهيئات أو الشخصيات على الاعتراف بعدالة القضية الجزائرية، أو يقدم أي صورة من صور الدعم لها مهما كانت بسيطة، بهدف محاصرة الثورة والقضاء عليها في مهدها، ثم استخلاص الدروس والعبر من كل ذلك، لاستثمارها في تنمية أواصر التضامن والتعاون المشترك بين البلدين والشعبين الشقيقين حاضرا ومستقبلا.
This paper aims to shed light on the various forms of political, financial, cultural, media and humanitarian support provided by Kuwait, officially and popularly, to the Algerian liberation revolution of 1954-1962,for religious, national, emotional and humanitarian considerations, and without condition or reciprocity as some have done. Kuwait supported the oppressed Algerian people in their struggle to get their freedom and achieve their sovereignty on their land, in spite of the pressure and the various threats, which were exercised and launched by the French higher authorities against anyone who dares to recognize the fairness of the Algerian case or provide any form of support. The French exercised their power to besiege the Algerian revolution and eliminate it in its infancy. Further more, we aim to draw lessons from all this support, to invest in the development of bonds of solidarity and cooperation between the two countries and the two peoples present and future.
Keywords: الكويت -- السياسة الخارجية -- ثورة التحرير الجزائرية -- الاحتلال الفرنسي للجزائر